COMPARATIVE CROSS-SECTIONAL STUDY OF BUCCOLINGUAL INCLINATION OF PERMANENT FIRST MOLAR IN DIFFERENT VERTICAL FACIAL PATTERNS IN A SAMPLE OF PAKISTANI POPULATION - Hussain, Mazhar; Faiza Malik,; Noman, Muhammad; Alamgir,; Hooria Haq,; Khan, Fiza (Journal of Ayub Medical College Abbottabad, 2025)
Background: Appropriate buccolingual inclination of posterior teeth and most favorable transverse width of maxillary arch are necessary to improve smile esthetics. The variability of buccolingual molar inclination in orthodontic literature, mainly in relation to vertical growth pattern of the face (Hyperdivergent, Normodivergent and Hypodivergent) is challenging for the orthodontist in choosing the treatment approach for addressing the problem in specific patients. Hence, the focus of this research was comparative assessment of buccolingual molar inclination in various vertical facial growth patterns. Methods: After obtaining ethical approval and informed consent, pre-treatment lateral cephalograms were taken to analyze vertical and sagittal craniofacial characteristics of orthodontic patients at Sharif Medical and Dental College, Lahore. The inclination of permanent first molars was measured on dental casts of orthodontic patients, by marking a perpendicular line to the occlusal table of first molar and a perpendicular line from the base of the cast. Angle formed between these lines was measured by protractor for all quadrants. Results: Seventy-five orthodontic patients were included in this cross-sectional study, where 44% were male and 56% were female. The frequency of normodivergent patients was 34.6%, hypodivergent was 34.6% and hyperdivergent was 30.6%. There was insignificant gender difference statistically in terms of buccolingual inclination of molars by applying independent t-test. The comparison of inter-study group (three groups) means of continuous variable was carried out with analysis of variance (ANOVA). There was significant difference in intergroup comparison based on Levene statistics (p<0.05). The statistical difference for buccolingual inclination of maxillary and mandibular first molar between groups based on Levene statistics and F value was significant (p=0.000 for all). Multiple comparison by Games-Howell Post-Hoc test was done for intergroup comparison after verifying significant difference by Levene statistic (p<0.05). Conclusion: In vertical growth pattern, the first molar teeth have a higher buccal inclination relative to horizontal or normal growth pattern. There was insignificant statistical difference between both genders in terms of buccolingual molar inclination.